2020
DOI: 10.1002/adfm.201910432
|View full text |Cite
|
Sign up to set email alerts
|

Pinning of the Fermi Level in CuFeO2 by Polaron Formation Limiting the Photovoltage for Photochemical Water Splitting

Abstract: CuFeO2 is recognized as a potential photocathode for photo(electro)chemical water splitting. However, photocurrents with CuFeO2‐based systems are rather low so far. In order to optimize charge carrier separation and water reduction kinetics, defined CuFeO2/Pt, CuFeO2/Ag, and CuFeO2/NiOx(OH)y heterostructures are made in this work through a photodeposition procedure based on a 2H CuFeO2 hexagonal nanoplatelet shaped powder. However, water splitting performance tests in a closed batch photoreactor show that thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 59 publications
2
26
0
Order By: Relevance
“…Alternatively, Jaegermann and co‐workers, claimed that FLP due to the formation and occupation of the bulk Fe 3+ /Fe 2+ electron polaron level precludes CuFeO 2 to develop the photovoltage for reaching the water reduction potential. [ 116 ] In a subsequent work, an IMPS analysis revealed that although bulk recombination was an important loss, the performance bottleneck for hydrogen production of CuFeO 2 electrodes synthesized by aerosol‐assisted chemical vapor deposition is surface recombination. [ 117 ] Many other reports have appeared in the last years pursuing both higher photoelectrochemical activity by using different synthetic routes and an in‐depth understanding of the PEC performance of this material.…”
Section: Ternary Oxides As Photocathodesmentioning
confidence: 99%
“…Alternatively, Jaegermann and co‐workers, claimed that FLP due to the formation and occupation of the bulk Fe 3+ /Fe 2+ electron polaron level precludes CuFeO 2 to develop the photovoltage for reaching the water reduction potential. [ 116 ] In a subsequent work, an IMPS analysis revealed that although bulk recombination was an important loss, the performance bottleneck for hydrogen production of CuFeO 2 electrodes synthesized by aerosol‐assisted chemical vapor deposition is surface recombination. [ 117 ] Many other reports have appeared in the last years pursuing both higher photoelectrochemical activity by using different synthetic routes and an in‐depth understanding of the PEC performance of this material.…”
Section: Ternary Oxides As Photocathodesmentioning
confidence: 99%
“…It has been reported that Fermi level pinning linked to the Fe 3+ /Fe 2+ couple hinders the HER reaction in this material. 129,130 Remarkably, NiFe an CoFe layered double hydroxides (LDHs) co-catalysts on CuFeO 2 have led to major improvements in the photoresponse. 127,128 Díaz-García et al 131 studied thin transparent CuCrO 2 films as photocathodes for water splitting synthesized by a simple sol-gel method.…”
Section: Water Photoreductionmentioning
confidence: 99%
“…Solar photocatalysis based on semiconductor materials is considered to be a promising technology, which can utilize solar energy to decompose organic contaminants. [ 8,9 ] However, due to the high recombination rate of charge carrier and low utilization efficiency of light energy, the photoenergy conversion efficiency of catalyst is still unsatisfactory, which seriously limits its practical application. [ 10 ] The key to break through this bottleneck is to design and develop new catalysts with good visible light response and high photocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%